Constitutional Court Decision Number 23/PUU-XIX/2021: Analysis of Judges' Considerations Is It Permissible to Take Cassation Against Decisions to Postpone Debt Payment Obligations? - Krista Yitawati; Pujiyono; Adi Sulistiyono (Universitas Muhammadiyah Surakarta, 2022)
ABSTRACT Purpose: This study aims to analyze the impact of the Constitutional Court's Decision Number 23/PUU-XIX/2021 regarding the permissibility of cassation in the Suspension of Debt Payment Obligations (PKPU). Methodology: The research method used by the researcher was a normative research method by reviewing statutory regulations and related legal materials. Results: The judge's consideration in the Constitutional Court's Decision Number 23/PUU-XIX/2021 is the permit of a cassation legal action against the decision on PKPU submitted by the creditor and the rejection of the offer of reconciliation from the debtor so that the court's decision on the PKPU application submitted by the creditor can be corrected as part of the control mechanism over court decisions at lower levels. However, with this decision, it is necessary to immediately issue implementing regulations regarding the mechanism for submitting PKPU and to control the good faith of creditors, so they do not actually injure. This is because the existence of debtors becomes a part of business actors playing a role in maintaining economic stability, so business continuity is sustained and is not misused. That being said, the legal certainty of the PKPU instrument can definitely be realized in accordance with the spirit of Law 37/2004, which is to provide legal protection for business actors. Applications of the study: It is expected that the legal certainty of the PKPU instrument can definitely be realized in accordance with the spirit of Law Number 37 of 2004, which is to provide balanced legal protection between debtors and creditors. Novelty/Orginalty of this study: This research is conducted due to the decision of the Constitutional Court Number 23/PUU-XIX/2021 that has recently been issued, the author analyzed the impact of the issuance of the decision on creditors and debtors. Keywords: Judges' Considerations, Decisions, Constitutional Court, PKPU